2002
DOI: 10.1111/j.1745-9133.2002.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Politically Popular Sentencing Policy: The Homicide Promoting Effects of “Three Strikes” in U.S. Cities (1980–1999)*

Abstract: Research Summary:Using panel data from 188 large cities during 1980-1999, we examined the possible homicide promoting effects of "three-strikes" laws. Results indicated that cities in states with three-strikes laws experienced short-term increases in homicide rates of 13% to 14% and longterm increases of 16% to 24% compared with cities in states without the laws. Policy Implications:Our results emphasize the fact that rarely are the possible unintended negative consequences of policy directives considered and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 30 publications
5
42
3
1
Order By: Relevance
“…County level estimates are on average lower than state level estimates, which in turn are lower than national level estimates [2,3,5,36]. While a strong negative relationship is present at the national level, this relationship mostly disappears at the county level [32,33].…”
Section: The Relationship Between Crime and Incarcerationmentioning
confidence: 88%
See 1 more Smart Citation
“…County level estimates are on average lower than state level estimates, which in turn are lower than national level estimates [2,3,5,36]. While a strong negative relationship is present at the national level, this relationship mostly disappears at the county level [32,33].…”
Section: The Relationship Between Crime and Incarcerationmentioning
confidence: 88%
“…They find that incarceration decreases crime but less so as the scale of incarceration increases. Kovandzic et al [32], Kovandzic and Vieraitis [33], and Kovandzic et al [34] provide evidence in support of the critical perspective at the city and county level. Clear et al [13] directly test the coercive mobility at the neighborhood level and also find some limited support for it.…”
Section: The Relationship Between Crime and Incarcerationmentioning
confidence: 90%
“…To the degree selective policies attain greater general and specific deterrence, a focus on just the incapacatative effects of selective policy underestimates the benefits of these selective policies (Shepherd 2002). However, to the extent implementation of a selective policy leads to a 'hardening' of crime-offenders facing long-term incapacitation going to extremes to avoid detection, even if for example this would mean they would have to kill for it (Kovandzic et al 2002;Marvell and Moody 2001;Shafer 1999)-a focus on incapacitation may in turn overestimate selective policies ultimate benefits. The model further assumes that others-who would not otherwise have offended-do not replace the incarcerated offenders.…”
mentioning
confidence: 99%
“…Census data permitted lower levels of analysis, but because this study contained data collected in yearly increments (as opposed to every ten years as in the census), the authors were forced to ''move up'' to the county-level. Some researchers used a technique called ''linear interpolation'' to ''fill in'' the annual gaps in census data (e.g., Kovandzic et al, 2002), but the authors of this article did not favor such an approach.…”
Section: In Defense Of Counties As the Units Of Analysismentioning
confidence: 96%
“…Recent studies showed that the ratio of police officers to citizens had an inverse effect on the crime rate (e.g., Kovandzic, Sloan, & Vieraitis, 2002;Marvell & Moody, 1996). As many, if not more, studies showed that police levels and the crime rate operated independently of one another (e.g., Loftin & McDowall, 1982).…”
Section: In Defense Of a Macro-level Analysismentioning
confidence: 97%